Sustainability consciousness among nursing students in Egypt: a cross-sectional study - Marwa Ahmed El-Sayed Mohamed; Eman Ghallab; Ragaa Abdullah Ahmed Hassan; Shaimaa Mohamed Amin (BMC, 2024)
Abstract Background Recognizing nurses as pivotal change agents and urgent preparation for the next generation is crucial for addressing sustainability issues and cultivating a sustainable healthcare system. Reports highlight gaps in the integration of sustainable development goals (SDGs) into nursing curricula, prompting the International Council of Nurses to stress the importance of sustainable development in nursing education. The extent to which nursing students are aware of sustainability issues remains to be determined. This study addresses a global and Egyptian research gap by evaluating and comparing Sustainability Consciousness (SC) levels among nursing students at three universities, providing insights into awareness, attitudes, and behaviors related to sustainability. Methods This descriptive comparative study was conducted across three nursing faculties within three Egyptian public universities. The target population for this study was undergraduate nursing students enrolled in these universities during the academic year 2022-2023. This study used the extended version of the Sustainability Consciousness Questionnaire (SCQ-L) to measure individuals' knowingness, attitudes, and behaviors related to the three dimensions of sustainable development: environmental, social, and economic. Results More than half of the nursing students across the three universities expressed unfamiliarity with the SDGs. Social media was the most common source of information across the three universities. Sohag University recorded the highest median (IQR) scores in sustainability knowingness (72.0, IQR: 70.0-81.0), attitudes (56.0, IQR: 53.0-61.5), and behavior (65.0, IQR: 60.0-69.0) across their respective dimensions, as well as in overall SC (195, IQR: 184.5-208.5). This was followed by Damanhour University, with a median score of 179.0 (IQR: 124.5-194), and then Alexandria University, with a median score of 116.0 (IQR: 85.5-153), all of which were significantly different (all with p values=0.000). Older students from rural areas exhibited higher SC median scores, while students with insufficient family income and no familiarity with the SDGs had lower SC scores. Conclusions This study highlighted the prevalent reliance on social media for information among nursing students across these universities, emphasizing the pivotal role of academic institutions in integrating sustainability development concepts in nursing education. Sohag University's notable commitment to sustainability practices has contributed to the higher SC of its students compared to Alexandria and Damanhour Universities. The study also identified age, place of residence, family income, and familiarity with the SDGs as consistent predictors of sustainability consciousness.